Electrospun Collagen-Coated Nanofiber Membranes Functionalized with Silver Nanoparticles for Advanced Wound Healing Applications - Martin Iurilli; Davide Porrelli; Gianluca Turco; Cristina Lagatolla; Alvise Camurri Piloni; Barbara Medagli; Vanessa Nicolin; Giovanni Papa (Membranes, 2025)
Complex wounds pose a significant healthcare challenge due to their susceptibility to infections and delayed healing. This study focuses on developing electrospun polycaprolactone (PCL) nanofiber membranes coated with Type I collagen derived from bovine skin and functionalized with silver nanoparticles (AgNPs) to address these issues. The collagen coating enhances biocompatibility, while AgNPs synthesized through chemical reduction with sodium citrate provide broad-spectrum antimicrobial properties. The physical properties of the membranes were characterized using scanning electron microscopy (SEM) and atomic force microscopy (AFM). Results showed the formation of nanofibers without defects and the uniform distribution of AgNPs. A swelling test and contact angle measurements confirmed that the membranes provided an optimal environment for wound healing. In vitro biological assays with murine 3T3 fibroblasts revealed statistically significant (p ≤ 0.05) differences in cell viability among the membranes at 24 h (p = 0.0002) and 72 h (p = 0.022), demonstrating the biocompatibility of collagen-coated membranes and the minimal cytotoxicity of AgNPs. Antibacterial efficacy was evaluated against Staphylococcus aureus (SA), Pseudomonas aeruginosa (PA), and Vancomycin-resistant Enterococcus (VRE), with the significant inhibition of biofilm formation observed for VRE (p = 0.006). Overall, this novel combination of collagen-coated electrospun PCL nanofibers with AgNPs offers a promising strategy for advanced wound dressings, providing antimicrobial benefits. Future in vivo studies are warranted to further validate its clinical and regenerative potential.